Harm reduction in relation to drug (Heroin) addiction: a comparative analysis from medical and Islamic perspectives - Abdul Razak, Tariq; Hashi, Abdurezak Abdulahi (Research Management Centre, International Islamic University Malaysia, 2016)
In the early 1980s, drug addiction was announced as a threat in Malaysia. “Cold Turkey” treatment and methadone replacement therapy has been initiated to address the problem. So far the treatment approaches did not achieve the expected target. Substitution therapy and harm reduction by supplying needless to the addicts to reduce infection especially HIV, has resulted in objections by certain groups and organizations from among Muslim community. Several issues related to shari’ah perspective on harm reduction have been raised also. This paper discusses medical and shari’ah perspectives on harm reduction in the treatment of drug abusers.